A revision of the genus Sinoxylon Duftschmid, 1825 (Sinoxylini: Bostrichinae: Bostrichidae: Coleoptera) - Liu, Lan-Yu (Zootaxa, 2026)
This study revises Sinoxylon Duftschmid, 1825, the largest genus in the family Bostrichidae. A key to the 48 species recognized is provided and descriptions and photographs of the species. Sinoxylon convexicauda Lesne, 1932b stat. nov. and S. spathiferum Lesne, 1906 stat. nov. are raised to species from subspecies of S. marseuli Lesne, 1895 and S. transvaalense Lesne, 1895 respectively. The following synonymy is proposed: Sinoxylon rejectum (Hope, 1845) (= S. eucerum Lesne, 1932b syn. nov.= S. japonicum Lesne, 1895 syn. nov.); Sinoxylon tignarium Lesne, 1902 (= S. mangiferae Chūjō, 1936 syn. nov.= Sinoxylon pygmaeum annamitumi Lesne, 1938 syn. nov.); Sinoxylon ruficorne Fåhraeus, 1872 (= S. erasicauda Lesne, 1906 syn. nov.= Sinoxylon ruficorne guineense Lesne, 1906 syn. nov.); Sinoxylon ceratoniae (L., 1758) (= S. succisum Lesne, 1895 syn. nov.); S. doliolum Lesne, 1906 (=S. cuneolus Lesne, 1906 syn. nov.); Sinoxylon atratum Lesne, 1897 (= Sinoxylon atratum kohlarianum Lesne, 1906 syn. nov.). It is confirmed that Apatodes macleayi Blackburn, 1889 nonem oblitum is conspecific with Sinoxylon anale Lesne, 1897 nomen protectum.